Effects of Ginseng Supplementation and Endurance-Exercise in the Artery-Specific Vascular Responsiveness of Diabetic and Sedentary Rats - Murias, Juan M.; Jiang, Mao; Dzialoszynski, Tomasz; Noble, Earl G. (Frontiers in Physiology, 2018)
This study examined the effects of 12 weeks North-American ginseng supplementation, exercise training, and sedentary behavior on vascular responses in type I diabetic rats. The following hypotheses were tested: 1) Ginseng supplementation would result in improved vascular responsiveness and sensitivity; 2) exercise training would result in further improvement in these vascular responses; 3) control rats with no access to exercise would show a depressed vascular response compared to control rats that were not exposed to a sedentary lifestyle. Groups: non-diabetic sedentary control (CS), sedentary diabetic (DS), sedentary diabetic with ginseng supplementation (DS+GS), diabetic with ginseng supplementation and high-intensity endurance exercise (D+GS+EX), and control not exposed to sedentary behavior (C). Diabetes was induced by streptozotocin. Arteries were excised, cleaned, and mounted onto a myography system. Percent vasorelaxation to acetylcholine (ACh) (10-8 M ACh to 10-4 M ACh) of the carotid artery was similar in CS (57±31%), C (66±35%), DS (58±36%), D+GS+Ex (71±37%), and DS+GS (64±37%) (p> 0.05). Percent vasorelaxation of the aorta was smaller in CS (23±17%) compared to C (46±35%), DS (60±40%), D+GS+Ex (64±40%), and DS+GS (56±39%) (p< 0.05), and smaller in C compared to D+GS+Ex (p< 0.05). In the femoral, the percent vasorelaxation was reduced in DS (18±16%) compared to all the other conditions (CS, 43±22%; C, 79.1±28%; D+GS+Ex, 55±27%; DS+GS, 45±26%; p< 0.05), but larger in C compared to the other conditions (CS, DS, D+GS+Ex, DS+GS; p< 0.05). Diabetes and sedentary lifestyle have detrimental effects on vascular responses that are evident in the femoral arteries of the diabetic rats. Ginseng supplementation restored the loss of sensitivity, with no added vascular protection of exercise training.